The Kullaberg peninsula – a glimpse of the Proterozoic evolution of SW Fennoscandia - Söderlund, Ulf; Karlsson, Christine; Johansson, Leif; Larsson, Kent (Taylor & Francis, 2008)
The Kullaberg peninsula in NW Skåne renders km-long, continuous exposures of the Proterozoic crystalline basement. We report ion microprobe (SIMS) U–Pb zircon ages for six key lithologies at Kullaberg that constrain the geological history of SW Fennoscandia for a considerable time period. Igneous zircon in three varieties of gneiss granite yield ages of 1694±7 Ma, 1693±7 Ma and 1663±14 Ma, in the same age range as orthogneisses further north in the same crustal segment. Partial melting, manifested by formation of pegmatite dykes and veins, occurred at 1473±6 Ma. Emplacement of mafic dykes, today seen as a large number of north-trending amphibolite sheets across the Kullaberg peninsula, is dated at 961±6 Ma. The dykes, which fall in the same age range as the Blekinge-Dalarna dolerites (978–945 Ma) predate an event of amphibolite facies deformation, which presumably relates to exhumation of the crust following shortly after the Sveconorwegian compressional stage. A pegmatite was emplaced at 934±6 Ma after the crust had been exhumed through the ductile-brittle boundary.